Physical Characterization on Hydrothermal Carbonization and Torrefaction Product from Wood Fibre Waste - Norfatin Sahira, Saidi (2013)
The world today is faced with serious global warming and environmental pollution. Besides that, the fossil fuel will become decrease in the near future and also increasing prices of fuel cause awareness to find alternative energy. Carbon is one of the most abundant elements found on earth. Nowadays carbon is really useful in the chemical industries and the demand of carbon used is high based on its applications towards the human needed. Carbonization is one of the possible thermo chemical conversions of biomass into energy, where a solid residue known as charcoal is produced through a slow process of partial thermal decomposition of in the absence or controlled presence of oxygen. (Bridgewater, 2003). There are three objectives that need to achieve at the end of this research. The objectives are; to develop and demonstrate the technology of hydrothermal carbonization process; to compare the carbon particles produce from HTC process and pyrolysis process; to study the effect of the wood fibre waste used towards the production of carbon. The HTC process occurs in the excess of water. About1 liter water was used for every experiment of hydrothermal carbonization process. The reaction is based on catalyst which is 50ml of citric acid was used for every experiment of hydrothermal carbonization process.the reaction occur in the supercritical unit for temperature about 200oC. The product obtained then was drying to remove the water contain. Second process which is the pyrolysis was run in the furnace by using the same operation condition as the HTC process. The differences between the process is the pyrolysis is no including water during the process. The process is about heating the wood fiber waste with absence of oxygen. Then the products were undergoing the physical characteristic testing by using Field Emission Scanning Electron Microscopy (SEM) and Nuclear Magnetic Resonance (NMR). After analyzing the sample from both process through FESEM and NM) the comparison was made. Through the FESEM characterization, the diameter of the sample and the morphology effect was determined. The comparison was made and the best sample shown by the sample from HTC process using 150g of wood fiber waste. The diameter of the sample shown about 7.3μm and the highest rupture occur at the surface of the particles. Results from NMR proves that the carbon content inside the sample was changes after undergo the HTC and pyrolysis process. The comparison was made and it shows that after undergo the HTC process the carbon content for cellulose and lignin was increased and HTC sample shows the content of aromatic lignin. Differ with pyrolysis process which does not contain aromatic lignin but for other content still increase after undergo the pyrolysis process. The proximate analysis also was done and it was found that HTC 175g WF gives the highest value of moisture content, HTC 150g WF gives the highest values of ash content with15.07%. for volatile content the highest values was the sample from pyrolysis 175g WF with 91.89% and lastly for calorific value proves the pyrolysis with 175g of WF give the highest calorific value with 24.88 MJ/kg.